2020
DOI: 10.1021/acs.jpcc.9b10607
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effects of Anion Substitution and Nanoconfinement on the Ionic Conductivity of Li-Based Complex Hydrides

Abstract: Solid-state electrolytes are crucial for the realization of safe and high capacity all-solid-state batteries. Lithium-containing complex hydrides represent a promising class of solid-state electrolytes, but they exhibit low ionic conductivities at room temperature. Ion substitution and nanoconfinement are the main strategies to overcome this challenge. Here, we report on the synthesis of nanoconfined anion-substituted complex hydrides in which the two strategies are effectively combined to achieve a profound i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
78
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(85 citation statements)
references
References 75 publications
7
78
0
Order By: Relevance
“…The pore size was determined by N 2 physisorption and turned out to be 8.7 nm. 11 The extra 30% was added to enable interconnectivity between the insulating alumina particles. The calculation was done after the specific pore volume has been determined via N 2 physisorption.…”
Section: Experimental Sectionmentioning
confidence: 99%
See 3 more Smart Citations
“…The pore size was determined by N 2 physisorption and turned out to be 8.7 nm. 11 The extra 30% was added to enable interconnectivity between the insulating alumina particles. The calculation was done after the specific pore volume has been determined via N 2 physisorption.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…During a dwell time of 30 min, LiBH 4 and LiI built a solid solution and infiltrate the pores of the alumina support. 53 For a more detailed description, we refer to our recent study, 11 which also includes the characterization of the reference samples LiBH 4 -LiI, i.e., a sample without alumina.…”
Section: Experimental Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies of combined effects of anion substitution and nanoconfinement [ 97 ] have shown that, for mixed-anion systems Li(BH 4 ) x I 1- x and Li(BH 4 ) x (NH 2 ) 1- x confined in nanoporous SiO 2 or Al 2 O 3 , the Li + conductivity at room temperature is higher than both the conductivities of the corresponding bulk materials and the conductivity of nanoconfined LiBH 4 . These results demonstrate that combining partial anion substitution and nanoconfinement may be a promising approach to reach high ionic conductivity at room temperature in complex hydrides.…”
Section: Effects Of Nanoconfinement On Dynamical Properties Of Hydmentioning
confidence: 99%